Prognostic Value of Serum Glucose Level in Septic Children in PICU - Wagley Poudel, Bulu; Rimal, Sabin; Gaire, Manisha; Rayamajhi, Ajit; Karki, Samikshya; Devkota, Ascol (Journal of Institute of Medicine Nepal, 2025)
Introduction Pediatric sepsis is a major cause of morbidity and mortality. Abnormal blood glucose is linked with higher mortality, increased requirement for mechanical ventilation and inotropic support. This study is aimed to determine the prognostic value of serum glucose level in sepsis children in PICU. Methods This retrospective study was performed in the Pediatric Intensive Care Unit (PICU) of Kanti Children’s Hospital with diagnosis of Sepsis from April 2024 to September 2024 with age ranging from 1 month to 14 years. The data was collected from the record section. The outcome of sepsis in the form of discharge or death during the hospital stay, length of hospital stay, use of ionotropic support, mechanical ventilation and blood sugar level were tabulated and the data analysis was done by SPSS version 21. Results Among 53 patients enrolled, 21 were male and 22 were female with male to female ratio of 1.4. The median age of the patient is 2.5±4.46 years. The median length of hospital stay was 7± 5days. There was no statistical significance in the length of PICU stay, use of ionotropic support and septic shock in patients with abnormal blood glucose. However, it was significantly associated with mortality (p value 0.009) and use of mechanical ventilator (p value 0.09). Conclusion Our study highlights that abnormal blood glucose level in pediatric sepsis is significantly associated with increased mortality and a greater need for mechanical ventilation. However, no significant relationship was observed between abnormal blood glucose, length of PICU stay and ionotropic support.